REINTERPRETATION OF UNDERSTANDING PANCASILA AND THE VALUE OF DIVERSITY POST-REFORM ERA : REINTERPRETASI PEMAHAMAN PANCASILA DAN NILAI-NILAI KEBHINEKAAN PASCA REFORMASI - Hamid, Rizal Al (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
The presence of Pancasila in the midst of the diversity of Indonesians is a gift in itself for every individual in this archipelago country. Besides it has a very high, comprehensive and general philosophical value, indirectly, Pancasila is always and is currently dealing with global ideologies, which according to some people are still controversial, such as capitalism, communism and liberalism. Because in this case, we feel greatly benefited by the founding fathers of this nation, where every point of the five precepts, which include divinity, humanity, unity, populism, and social justice, has represented a very heterogeneous and heterogeneous population entity of the State. As if it is an inseparable unity, Pancasila is often combined with multicultural values because of the diversity of its inhabitants, both culturally, in customs, in lifestyle, to belief in their God. So in this case it can be said that multiculturalism is a real form and a portrait of our country, and Pancasila is the device or tool. As a pillar and portrait of the reality of our country, Pancasila and the plurality of its citizens have, are, and will always experience various perspectives of studies, interpretations, and the accompanying polemics, especially in post-reformation. In this simple article, we will explore how the twists and turns of Pancasila in this multicultural nation, especially after the fall of the new order.